1995
DOI: 10.1007/bf02327577
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hyperactivity scores are highly heritable and show sibling competition effects: Twin study evidence

Abstract: Hyperactivity has consistently been shown to be familial. Until recently however, due to a lack of systematic twin evidence, it has remained uncertain to what extent familial transmission can be explained by genetic factors. We used a systematically ascertained population-based sample of twin pairs aged between 8 and 16 years old to explore the role of genetic influences on maternally rated hyperactivity scores. Hyperactivity scores were found to be substantially heritable. The data were best explained by a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
104
7
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 32 publications
16
104
7
3
Order By: Relevance
“…4 unknown, but a substantial genetic element exists. This has been demonstrated by family (Biederman et al 1990(Biederman et al , 1992Faraone et al, 1992Faraone et al, , 1994, twin (Thapar et al 1995;Silberg et al 1996;Levy et al 1997), and adoption studies (Alberts-Corush et al 1986; Cadoret and Stewart 1991). The heritability (h 2 ) of ADHD has been estimated to be .50-.98 (Gjone et al 1996;Levy et al 1997).…”
mentioning
confidence: 84%
“…4 unknown, but a substantial genetic element exists. This has been demonstrated by family (Biederman et al 1990(Biederman et al , 1992Faraone et al, 1992Faraone et al, , 1994, twin (Thapar et al 1995;Silberg et al 1996;Levy et al 1997), and adoption studies (Alberts-Corush et al 1986; Cadoret and Stewart 1991). The heritability (h 2 ) of ADHD has been estimated to be .50-.98 (Gjone et al 1996;Levy et al 1997).…”
mentioning
confidence: 84%
“…Importantly from the molecular genetics perspective, many twin studies have found zero or even negative dizygotic (DZ) twin correlations and concordance rates for maternally reported ADHD defined using questionnaire measures and interviews. 18 Low DZ twin correlations could possibly arise from sibling competition, with increased ADHD scores in one twin leading to lower scores in the co-twin 26 or rater contrast effects 27 whereby mothers maximise the contrast between their DZ twin children. However rater contrast effects have not been found in all studies and may differ depending on the type of measure used.…”
Section: Parent Reportsmentioning
confidence: 99%
“…6 Studies of siblings of children with ADHD also suggest that ADHD is familial. [7][8][9][10][11][12] Data from twin studies of ADHD 13 show an average heritability of 0.76, among the highest in psychiatric disorders, attributing about 80% of the population variance of ADHD to genetic factors.…”
Section: Introductionmentioning
confidence: 99%